A vevőelégedettség biztosítása az önkormányzatoknál Marketing Controlling segítségével - Boll, Anikó (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The city marketing is a method covering a big area and prevents the loss the competi-tion marketability between the cities, and inside the office planning serves it. In this case is the city as a product, which can be marketable with an attractive and wide scale of supply, in this case, product like that, than everything else, which it is necessary to advertise and to sell with a conscious marketing strategy. The city is marketable and must to sell for his inhabitant, the tourist, the investors and then for a row of additional target group. "The company, who does not draw up his future, there hasn't future". (H. Ansoff). If the tourist returns, if the inhabitant lives with pleasure in the city and the investor settles down, he creates a workplace, we may talk about a satisfied customer then. The not profit-oriented organisations differ from the companies in it fundamentally, that here the primary one (strategic) targets not the increase of the profit acquisition, the property, but the direct satisfaction of one of the social-environmental requirement. His longer time a lasting eco-nomic crisis hurries the solution of those tasks only, which ones a big burden was imposed on the local governments till now. From a source standing for increasingly fewer provisions at what more have to be accomplished, otherwise the customer satisfaction is can-celled and the customer opts for an other product. The key of the business relationships working well on the long distance is customer satisfaction.